The applicability of a portable electronic falls diary to assess fall frequency in Parkinson’s disease - Domingos, Josefa (2016)
"Background: Although falling is a frequent occurrence in Parkinson disease, the best method(s) for measurement of falls remains unclear. Paper and electronic “falls diaries” are commonly used in health care and clinical research to assess the frequency and circumstances of falls and near fall events. However, there is a lack of objective documentation of the applicability of such diaries and limitations with respect to their use in both paper and electronic formats, which may ultimately affect the ability of these instruments to assess falls effectively."